The improvement of leaming ability by means of reading - Morles, Armando (1997)
This study discusses the importance of instruction in the ability to learn from texts. First learning through reading is defined, followed by the identificaction of the factors that determine this learning. It provides guidelines for the improvement uf such an ability. Finally, it gives i'deas about ways of conducting the student training, including exercising modalities and the program placement in the educational context.